Strategi Pemasaran pada Inovasi Produk Berbasis Ubi: Ubique: Ubi Crème Brulee - Muhammad Agung Hudaya; Awin Mulyati (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This study examines the marketing strategy for Ubique (Ubi Crème Brulee), an innovative product based on sweet potatoes, using the 4P marketing mix approach (Product, Price, Place, Promotion). A qualitative case study method was employed through interviews, observations, and analysis of marketing materials. The findings reveal that product innovation combining local ingredients with international flavors, affordable premium pricing strategies, creative distribution channels such as Demo Day, and promotion through digital media and Word of Mouth were key success factors. These results highlight further development opportunities to expand market reach and enhance Ubique's competitiveness.